A Bioinspired Hierarchical Fast Transport Network Boosting Electrochemical Performance of 3D Printed Electrodes. Issue 35 (26th October 2022) - Zhao, Bo; Wu, Jiawen; Liang, Zhiqiang; Liang, Wenkai; Yang, He; Li, Dan; Qin, Wei; Peng, Meiwen; Sun, Yinghui; Jiang, Lin
Abstract: Current 3D printed electrodes suffer from insufficient multiscale transport speed, which limits the improvement of electrochemical performance of 3D printed electrodes. Herein, a bioinspired hierarchical fast transport network (HFTN) in a 3D printed reduced graphene oxide/carbon nanotube (3DP GC) electrode demonstrating superior electrochemical performance is constructed. Theoretical calculations reveal that the HFTN of the 3DP GC electrode increases the ion transport rate by more than 50 times and 36 times compared with those of the bulk GC electrode and traditional 3DP GC (T‐3DP GC) electrode, respectively. Compared with carbon paper, carbon cloth, bulk GC electrode, and T‐3DP GC electrode, the HFTN in 3DP GC electrode endows obvious advantages: i) efficient utilization of surface area for uniform catalysts dispersion during electrochemical deposition; ii) efficient utilization of catalysts enables the high mass activity of catalysts and low overpotential of electrode in electrocatalytic reaction. The cell of 3DP GC/Ni‐NiO||3DP GC/NiS2 demonstrates a low voltage of only 1.42 V to reach 10 mA cm −2 and good stability up to 20 h for water splitting in alkaline conditions, which is superior to commercialized Pt/C||RuO2 . This work demonstrates great potential in developing high‐performance 3D printed electrodes for electrochemical energy conversion and storage. Abstract : A 3D printed reduced graphene oxide/carbon nanotube (3DP GC) electrode with a bioinspired hierarchical fast transport network is reported, which demonstrates superior electrochemical performance. This is the first study to systematically investigate the hierarchical mass transport properties of 3D printed electrodes and reveal the promoting effect of multiscale fast mass transport on the electrochemical performance of 3D printed electrodes.